marketing plan 2017 - Ruwida, Omar (Libyan International Medical University Faculty of Pharmacy, 2017)
Marketing Plan 2017
The faculty of pharmacy have prepared a strategic plan for marketing and advertising its newly launched program (Pharm D program) from 1/March/2017 to 26/May/2017. All staff and some of the students have participated in in the plan to introduce the program as well as attracting potential customers.
Keywords: Faculty of Pharmacy; marketing; Marketing Plan